2022
DOI: 10.1002/jmv.27792
|View full text |Cite
|
Sign up to set email alerts
|

Longer length of stay, days between discharge/first readmission, and pulmonary involvement ≥50% increase prevalence of admissions in ICU in unplanned readmissions after COVID‐19 hospitalizations

Abstract: Hospital readmissions due to COVID-19 are one of the main concerns for the health system due to risks to the patient's life and increased use of health resources.Studies focusing on this issue are important to understand the risk factors and create strategies to avoid readmissions. We evaluated the readmission of patients with confirmed COVID-19 in a private hospital in southern Brazil, between March 2020 and 2021. Also, the characteristics and clinical outcomes of patients admitted to the intensive care unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
(89 reference statements)
0
10
0
1
Order By: Relevance
“…Interestingly we note that patients who were admitted to the ICU had higher LOS. Despite administrative prioritization to reduce LOS and ICU admission, studies about COVID‐19 have suggested these two outcomes may be related 13,15–17 . Reducing LOS during the COVID‐19 pandemic has also been emphasized to preserve resources and limit exposure.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly we note that patients who were admitted to the ICU had higher LOS. Despite administrative prioritization to reduce LOS and ICU admission, studies about COVID‐19 have suggested these two outcomes may be related 13,15–17 . Reducing LOS during the COVID‐19 pandemic has also been emphasized to preserve resources and limit exposure.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the spread of the omicron variant has returned the alert for the progression and evolution of the pandemic, even though mass vaccination and herd immunity were already established, the number of cases and occupations in the intensive care unit (ICU) were worrying between January and March 2022 10–12 . In this sense, it is essential to study the outcomes of hospitalizations, ICU admission, use of mechanical ventilation, readmissions, and lethality to qualify and quantify the impact of COVID‐19 on the hospital system 5–9,13–15 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations